Arm coordination, active drag and propelling efficiency in front crawl - Seifert, L.; Schnitzler, C.; Alberty, M.; Chollet, D.; Toussaint, H. M. (Biomechanics and Medicine in Swimming XI, 2010)
Active drag, regularity and Index of Coordination (IdC) all increase with speed (v) in front crawl swimming, but the link between those parameters remains unclear. The aim of this study was thus to examine the relationships between the index of coordination (IdC) and propelling efficiency (ep) and the active drag (D). Thirteen national level male swimmers realised two incremental speed tests swimming front crawl with arms only in free condition and using a Measurement of Active Drag (MAD) system. D was measured using the MAD-system; ep was assessed by the ratio v3free / v3MAD; IdC was obtained from arm stroke phases evaluation using video device. The results showed that inter-arm coordination was linked to active drag and not propelling efficiency. Significant quadratic regression between IdC and v (0.91<R²<0.99), power regression between D and v (0.93<R²<0.98) and linear regression between IdC and D (0.64<R²<0.98) were established for each swimmer.